Acute hormonal and myokine responses to traditional vs. circuit resistance training in high-BMI and low-BMI males - Seyed Saeid Kazemi Rezaei; Moein Fasihiyan; Behrad Boron; Maryam Nourshahi (Journal of Exercise & Organ Cross Talk, 2025)
This study examined the acute hormonal and myokine responses to traditional and circuit resistance training in young males with distinct BMI-based groups. Twenty sedentary men aged 20–30 years were classified as high-BMI (BMI >29.9) or low-BMI (BMI <18.5). Each participant completed both traditional resistance training (TRT) and circuit resistance training (CRT) protocols in a crossover design, with a one-week washout period. Sessions included multi-joint upper and lower body exercises at comparable intensities. Blood samples were taken immediately before and after each session. Serum levels of testosterone, cortisol, myostatin, and follistatin were assessed using ELISA kits. A repeated-measures ANOVA was used to compare within- and between-group changes across time and training modality. Baseline cortisol levels were significantly higher in low-BMI individuals (P=0.037), while testosterone levels showed no initial difference between groups (P>0.05). Post-TRT, testosterone levels increased significantly in high-BMI individuals compared to low-BMI individuals (P=0.017), with both training types elevating testosterone and cortisol across all participants (P<0.05). CRT led to a significant reduction in myostatin and increase in follistatin in high-BMI individuals (P<0.05), while only follistatin increased significantly in low-BMI individuals after TRT (P<0.05). These results suggest that CRT promotes superior anabolic signaling in high-BMI individuals, while TRT is more effective at enhancing testosterone response. Myokine and hormonal responses appear to be body-type-dependent and training-modality-specific. Practitioners designing hypertrophy-focused programs should tailor training protocols to the athlete’s BMI-based group to optimize muscle adaptation and endocrine outcomes. And also, trainers should individualize hypertrophy programs based on body composition to optimize both hormonal responses and muscle adaptation.